Customer Satisfaction as a Mediating Mechanism of Banking Loyalty: An Empirical Re-analysis of the Corporate Image and Service Quality Model among Bank BRI Customers - Muhamad Arif Wiyanto; Dahlan Hidayat (Sanskara Manajemen Dan Bisnis, 2026)
This study was conducted to reinterpret the role of customer satisfaction as a mediating variable in the formation of customer loyalty at Bank Rakyat Indonesia (BRI) based on recent theoretical developments, as well as to identify strategies that can be employed to enhance customer loyalty in the digital banking era. A quantitative approach was adopted using a secondary data analysis design through the empirical re-analysis method. The data were obtained from Hidayat (2019), which examined the effects of corporate image and service quality on customer loyalty through customer satisfaction at Bank BRI Purwokerto Branch, involving 144 respondents and utilizing the Structural Equation Modeling (SEM) approach. In this study, neither primary data collection nor re-estimation of the SEM model was conducted. Instead, the research focused on reinterpreting the empirical findings, including goodness-of-fit measures, direct effects, and indirect effects among variables. The results of the interpretation indicate that service quality is the most dominant factor in enhancing customer satisfaction and customer loyalty. Positive customer experiences that promote satisfaction and loyalty were found to be created through services that are fast, reliable, secure, and supported by user-friendly digital platforms. In contrast, the direct effect of corporate image on customer loyalty was not found to be significant, suggesting that loyalty is shaped more by service quality and customers’ actual experiences than by image perceptions alone. Furthermore, the mediating role of customer satisfaction in the relationship between service quality, corporate image, and customer loyalty was successfully confirmed. Based on these findings, the enhancement of customer experience, the strengthening of service quality, and the continuous development of digital banking services are recommended to be prioritized by BRI in order to increase customer satisfaction and build stronger and more sustainable customer loyalty amid omnichannel banking competition.